Assessment of the awareness and attitude of the last years dental students at Yazd Shahid Sadooghi medical school regarding consultation on smoking cessation for patients - Arezoo Khabazian; Pooya Fadaei Tehrani; Ali Tavakoli; Amir Kheyrossadat (Tehran University of Medical Sciences, 2019)
Background and Aims: Today, smoking is recognized as a major health problem and an impediment to development in many developing countries. This is the reason of early deaths and disabilities which leads to death of about 4 million people around the globe annually. This study aimed at assessing the awareness and attitude among the students last years dental at Yazd Shahid Sadooghi Medical School in providing consultation for giving up smoking. Materials and Methods: This study was a descriptive sectional study that evaluated the awareness and attitudes of students last years dental at school of dentistry. Data was collected through standard questionnaires and were analyzed by T test and Pierson correlation coefficient in SPSS18 software. Results: A total of 110 students participated in this study. Awareness mean's score of female students was 18.38 and male students 17.66. The attitude mean's score of female students was 31.06 and the male students was 32.45. Based on the correlation coefficient of awareness with age (0.112), with the semester (-0.001) and with a GPA (0.76), it was concluded that awareness with increasing age and GPA increased, and with increasing semester decreases. Also, based on the correlation coefficient of attitude with age (0.013), with the academic semester (0.018) and with a GPA (0.008), it was concluded that attitude with increasing age, semester, and GPA was improved. Conclusion: Despite the relatively good attitude of dental students about smoking cessation counseling, their awareness was poor. Therefore, the need to revise the education programs and steps in the field of training are required.